2020
DOI: 10.51791/njap.v46i2.45
|View full text |Cite
|
Sign up to set email alerts
|

Piliostigma thonningii leaves as dry season feed supplement for West African dwarf goats

Abstract: A persistent issue with ruminant production during the dry season in the tropics is scarcity of forages. Producers are faced with the search for alternative feed supplements to address this issue without compromising productivity. Acceptability of Piliostigma thonningii as dry season feed supplement to West African dwarf (WAD) goat was investigated in this study. The WAD goats (n=15) were divided into three treatments of five goats each in a completely randomized design. The animals were fed with Panicum maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…[ 59 ], and Ayenew [ 9 ]. In agreement with this study, the findings of Jimoh and Oladiji [ 13 ], Bekele and Tengnäs [ 3 ], Orwa et al [ 1 ], Egharevba and Kunle [ 11 ], Chidumayo [ 10 ], and Jemiseye et al [ 12 ] revealed that the pods are nutritious and preferred by domestic animals such as cattle and browser wild animal species such as the African elephant and antelopes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[ 59 ], and Ayenew [ 9 ]. In agreement with this study, the findings of Jimoh and Oladiji [ 13 ], Bekele and Tengnäs [ 3 ], Orwa et al [ 1 ], Egharevba and Kunle [ 11 ], Chidumayo [ 10 ], and Jemiseye et al [ 12 ] revealed that the pods are nutritious and preferred by domestic animals such as cattle and browser wild animal species such as the African elephant and antelopes.…”
Section: Discussionsupporting
confidence: 90%
“…Sources show that the different parts of the tree (leaves, pods, and seeds) which are nutritious are browsed by animals including elephants, livestock, and antelopes [ 1 , 10 – 13 ]. The leaves of P. thonningii are eaten and chewed by the Masai people to relieve thirst [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaves are used as food in the Benna-Tsemay and Hamar Districts of the South Omo Zone (Hailemariam et al, 2021;Paulos et al, 2016) and also consumed by animals as fodder (Tadesse et al 2012, Amente, 2017, Tebkew et al, 2018and Ayenew 2019. The leaves are eaten and chewed by the Masai people to relieve thirst (Jemiseye et al, 2019). The wood is suitable for poles, firewood, charcoal, carpentry and construction, to while the bark is used for making strings and ropes (Orwa et al, 2009;Chidumayo, 2018).…”
Section: Introductionmentioning
confidence: 99%